Master plan as a legal instrument for organization of urban space (Revista do Tribunal Regional Federal da 3ª Região, 2019)
The Federal Constitution has raised the master plan to the status of being a fundamental legal resource for organization of urban space (article 182). However, doubts on the application of the law that laid down the plan are not uncommon. The relationship of the master plan with other laws dealing with urban matters still raises important doctrinal and jurisprudential controversies. This is mainly due to traditional ways of resolving conflicts between legal norms - which do not apply to the antinomies existing between the law establishing the master plan - and other local urban laws. There are some concerns as to how far the autonomy of the municipal / district legislation goes in so far as handling urban land occupation, in view of the so-called principle of plan competence; it is questioned, for example, if local laws can regulate urban planning instruments not contemplated in the master plan, such as residential lands, for one. In fact, the topic was subject to appraisal by the Federal Supreme Court, in the judgment of Extraordinary Appeal No. 607.940-DF, which will be object of analysis in a specific chapter. The present study intends to address these and other issues, such as the specific legislative procedure for editing the master plan, the scope of the plan, its change, its minimum content and its periodic review process.
Keywords: urban planning; master plan; town planning instrument; principle of plan competence